The Implementation of PINDU (Center for Information and Complaints) Program Innovation Policy in Pinrang District - Inten Suweno Anugraha; Fernando Fernando (Research and Development Agency Ministry of Home Affairs, 2017)
This study aims to examine the implementation of PINDU (Center for Information Services and Complaint) Program Policy Innovation in Pinrang District. This study is a study of innovation implementation using factor structure indicators, namely rules and communication, incentive, openness, and balance. This research is qualitative. Data collection is done through observation, interview, and literature. Data from observations and interviews are presented in the form of documentation of the research object. Data from the literature results are presented in the form of quotations to reinforce the research findings. The data obtained are analyzed and processed using phenomenology technique. The results show that the rules in PINDU are very clear which is seen from Regulation of Regent Number 25 of 2014 about PINDU Formation of Pinrang District Government and from Standard Operational Procedure (SOP) of PINDU. The rules have been well implemented by PINDU officers as well as by PINDU users. By complying with existing rules, then the exchange of information is very smooth and clear. Completeness of facilities and infrastructure in PINDU indicates the existence of incentives in PINDU. In addition, openness between structures is also very open so that officers are able to balance between professionalism in working with the influence of interested groups. Thus, the implementation of PINDU program policy innovation can be said to run in accordance with existing indicators. However, there are still some indicators that need to be improved, i.e. indicators of communication and openness to the public.